On the Differentiation of Lexical Archaisms and Innovations in Old Church Slavonic Text: Variants kъnižnikъ and kъnigъčii in Gospel Manuscripts from the 11th–16th Centuries - Темчин, С. Ю. (Kalbotyra, 1997)
This paper discusses seven formal criteria to distinquish lexical archaisms and innovations in a large body of manuscript copies of the same Old Church Slavonic text. The potentialities of these criteria are demonstrated with the example of the synonimic pair kъnižnikъ and kъnigъčii γραμματεύζ, used in numerous manuscript copies of the Gospel text from the 11th-16th centuries. The criteria are the following: 1) dispersion of competitive lexical variants in the text; 2) number of text points, in which alternative variants are used exclusively; 3) number of the manuscript copies presenting one variant exclusively; 4) dating and localization of the manuscripts, in which the less common variant is more frequent; 5) ratio of text points, where alternative lexemes are used hypercorrectly; 6) distribution of the less common lexeme in manuscript copies; 7) determination of other literal monuments, in which the lss common variant is more frequent.